Occurrence and characterization of multidrug-resistant extended spectrum β-lactamase producing Escherichia coli from bovine mastitis of Haryana - MANOJ, JINU; KAMBOJ, SARIN; CHHABRA, RAJESH; SINGH, MAHAVIR (The Indian Journal of Animal Sciences, 2024)
A study was carried out to analyze 500 bovine milk samples collected from Haryana, India and 37% samples were found to be associated with E. coli as a causative agent for mastitis. Out of it, 53 (10.6%) isolates were found to be positive for ESBL production by Double-Disk Synergy test and Epsilon test. However, the ESBL-encoding gene blaCTX-M was detected in the 51 (10.2%) isolates. The antibiotic susceptibility test revealed 13.72% of the isolates were multidrug resistant, with MAR index varying from 0.06 to 0.46. The maximum sensitivity was observed towards gentamicin (90.19%) followed by chloramphenicol (78.4%). Fluoroquinolones antibiotics were found to be resistant between 84.31% to 76.47%. The resistance profile underscores the importance of antibiotic stewardship and the need for ongoing surveillance using one health approach to guide therapy and manage the spread of resistant bacteria.